Heteromorphism of sperm axonemes in a parasitic flatworm, progenetic Diplocotyle olrikii Krabbe, 1874 (Cestoda, Spathebothriidea) - Bruňanská, Magdaléna; Matoušková, Martina; Jasinská, Renáta; Nebesářová, Jana; Poddubnaya, Larisa G (Parasitology research, 2020)
The spermatozoon ultrastructure of the progenetic cestode Diplocotyle olrikii (Spathebothriidea) has been examined using transmission electron microscopy and cytochemical staining with periodic acid-thiosemicarbazide-silver proteinate (PA-TSC-SP) for glycogen. The spermatozoon is a filiform cell, tapered at both extremities. Its moderately electron-dense cytoplasm possesses two parallel axonemes of unequal lengths. New for the Cestoda is a finding of three types of the mature spermatozoa with respect to different axonemal structure. The first type has both axonemes with standard 9 + '1' trepaxonematan pattern. The second type is represented by a spermatozoon having one axoneme with 9 + '1' structure and the second one with 9 + 0 pattern. The third type includes the two axonemes with 9 + 0 pattern. Microtubule doublets of the 9 + 0 axonemes contain either inner dynein arms or no dynein arms. In addition to the two axonemes, all three types of the mature sperm cells contain parallel nucleus, parallel cortical microtubules, four electron-dense plaques/attachment zones, and glycogen. The anterior extremity of the gamete exhibits a centriole surrounded by a semiarc of up to five electron-dense tubular structures. The distal end of the first type spermatozoa exhibits two morphological variants, represented either by (i) nucleus or (ii) remnants of the disorganized axoneme. Distal extremity of the spermatozoa of the second and third types contains doublets and singlets of disorganized axoneme. The ultrastructural characters of the spermatozoon of progenetic D. olrikii support the basal position of the Spathebothriidea within the Eucestoda.
Keywords: Spermatogenesis; Axoneme; axonema; Cytoplasm; Cell Nucleus; buněčné jádro; Microscopy, Electron, Transmission; Spermatozoa; spermatogeneze; Cestoda; transmisní elektronová mikroskopie; centrioly; mužské pohlaví; spermie; zvířata; Animals; Male; Centrioles; cytoplazma